Facial Neuritis as a Manifestation of Gradenigo's Syndrome - Kentab, Amal Y.; Kentab, Osama Y. (Journal of Pediatric Neurology, 2021)
Gradenigo's syndrome (GS) is a rare, acquired syndrome caused by middle ear infections or mastoiditis. It is identified by the triad of otorrhea due to otitis media (OM), retro-orbital pain in the region innervated by the first and second divisions of the trigeminal nerve, and diplopia as a result of cranial nerve (CN) VI palsy. As a result of extension of the inflammation, the facial nerve (VII) may also be affected. GS has a poor prognosis unless promptly diagnosed and treated. Herein, we report the clinical and radiological findings observed in two children diagnosed with chronic suppurative OM, mastoiditis, and facial neuritis. Both were medically managed as cases of GS with high-dose intravenous antibiotic and full recovery was achieved a few weeks after discharge. There was no need for any surgical intervention. This case report illustrates the importance of early recognition, diagnosis, and treatment of this treatable syndrome using antibiotics to prevent subsequent fatal complications and further need for surgical intervention.
Keywords: Gradenigo's syndrome; acute otitis media; petrositis; Bell's palsy; abducens palsy